2009
DOI: 10.1242/jeb.025700
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-specific induction of endocytosis in taste receptor cells

Abstract: SUMMARYBehavioural experiments demonstrated that Texas Red dextran is a deterrent taste substance for brown trout. In fish first exposed to the stimulant L-cysteine plus a dye and subsequently to a deterrent, either Texas Red, or glycine, the majority of stained cells were found in separate taste receptor cells, indicating that the majority of taste receptors for stimulants and deterrents are expressed in separate taste buds. These results also strengthen the assumption that the stained cells take part in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…We found ligand-specific endocytosis in taste receptor cells of brown trout, Salmo trutta, and hypothesized that ligand-specific receptor-mediated endocytosis may be a common phenomenon in all types of vertebrate chemosensory neurons (Døving et al, 2009). In the present study we examined this question using mainly crucian carp, which exhibits a distinct organization of the olfactory system (Hamdani and Døving, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…We found ligand-specific endocytosis in taste receptor cells of brown trout, Salmo trutta, and hypothesized that ligand-specific receptor-mediated endocytosis may be a common phenomenon in all types of vertebrate chemosensory neurons (Døving et al, 2009). In the present study we examined this question using mainly crucian carp, which exhibits a distinct organization of the olfactory system (Hamdani and Døving, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Individual taste receptor cells are dedicated to the transduction of only one taste quality, but TBs contain a combination of differently tuned taste cells (Aihara et al, ; Døving et al, ). It has also been demonstrated that responsiveness to taste ligands is the same in different areas of the fish oral cavity (Devitsina et al, ) suggesting that, contrary to popular belief, there is no tongue map in fishes, as was previously disproved in mammals as well (Chandrashekar et al, ).…”
Section: The Anatomy and Physiology Of The Taste System In Fishesmentioning
confidence: 99%
“…Advanced immunohistochemical details could primarily establish their function in relation to food selection and rejection. For further details to ascertain such relationship, ligand-specific induction using fluorescent dye may be applied followed by histomicrography of samples (Døving et al 2009). …”
Section: Figure 4 (A) Costello's (1990) Graphical Plot For Predator Fmentioning
confidence: 99%